2007
DOI: 10.1093/pcp/pcm022
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Type-A Response Regulator Alters Rice Morphology and Cytokinin Metabolism

Abstract: Genome-wide analyses of rice (Oryza sativa L.) cytokinin (CK)-responsive genes using the Affymetrix GeneChip(R) rice genome array were conducted to define the spectrum of genes subject to regulation by CK in monocotyledonous plants. Application of trans-zeatin modulated the expression of a wide variety of genes including those involved in hormone signaling and metabolism, transcriptional regulation, macronutrient transport and protein synthesis. To understand further the function of CK in rice plants, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
159
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(170 citation statements)
references
References 90 publications
10
159
0
1
Order By: Relevance
“…The exogenous application of CK to Arabidopsis (Arabidopsis thaliana) seedlings resulted in the reduced expression of AtNRT genes (encoding nitrate transporters) as well as some ammonium and amino acid transporters (Kiba et al, 2011). A similar CK-induced down-regulation of genes associated with nutrient acquisition was reported in 2-week-old rice seedlings grown hydroponically and treated with exogenously applied CK (Hirose et al, 2007). Since the CK-induced repression of AtNRT genes was observed under both low and high N, it was suggested that the CK effects were independent of the N status of the plant (Kiba et al, 2011).…”
Section: Gs Nadh-gogat Gdh Amination [Gdh a ] And Deamination [Gdh mentioning
confidence: 56%
“…The exogenous application of CK to Arabidopsis (Arabidopsis thaliana) seedlings resulted in the reduced expression of AtNRT genes (encoding nitrate transporters) as well as some ammonium and amino acid transporters (Kiba et al, 2011). A similar CK-induced down-regulation of genes associated with nutrient acquisition was reported in 2-week-old rice seedlings grown hydroponically and treated with exogenously applied CK (Hirose et al, 2007). Since the CK-induced repression of AtNRT genes was observed under both low and high N, it was suggested that the CK effects were independent of the N status of the plant (Kiba et al, 2011).…”
Section: Gs Nadh-gogat Gdh Amination [Gdh a ] And Deamination [Gdh mentioning
confidence: 56%
“…While N remobilization is vitally important for grain filling, cytokinin signaling has been shown to influence rice stem length and spikelet branching and, thus, at least in part controlling yield (Ashikari et al, 2005;Hirose et al, 2007;Tabuchi et al, 2007;Zhang et al, 2010). Overexpression of Cga1 shows similar potential for increasing yield via altering panicle architecture; however, constitutive overexpression resulted in detrimental effects with respect to grain filling.…”
Section: Cga1 Shows Potential For Utilization In Crop Improvementmentioning
confidence: 99%
“…Furthermore, cytokinin signaling mediates many of the effects of applied N and can mimic these responses in the absence of N (Sakakibara, 2003;Sakakibara et al, 2006). Both cytokinin application and the modification of genes involved in cytokinin signaling influence chloroplast development, rice plant architecture, and yield (Ashikari et al, 2005;Hirose et al, 2007). As such, understanding the links between N, cytokinin, and GA signaling is also important for making improvements in agricultural crops.…”
mentioning
confidence: 99%
“…In order to examine transcript abundance changes across different tissues, under different conditions, and compare these with the transcript abundance profiles generated from this study, rice array data were retrieved from the Gene Expression Omnibus within the National Center for Biotechnology Information database as described previously ) with the addition of data derived from cytokinin treatment of roots and leaves (GSE6719; Hirose et al, 2007) and infection with Striga hermonthica (GSE10373; Swarbrick et al, 2008).…”
Section: Public Rice Microarray Data Analysis and Comparisonmentioning
confidence: 99%